Pengolahan Kripik Tortilla Jagung di Desa Bantul, Kapanewon Bantul, Kabupaten Bantul, Daerah Istimewa Yogyakarta - Purnomo, Prasetyo Sidi (Lembaga Penelitian dan Pengabdian pada Masyarakat, 2023)
Implementation of community service activities in the form of observation and village development in Bantul Village, Kapanewon Bantul, Bantul Regency, Special Region of Yogyakarta. Research and Implementation of the Work Program were carried out boldly, due to the COVID-19 conditions. Research on the use of natural resources in Bantul Village, to improve the welfare and economic conditions of the Bantul Village community. Community service activities begin by identifying problems and potential resources in the Bantul Village area. The activity continued with the making of work programs, selection of service methods, and output products, followed by evaluation of the work programs that had been made. The final process is to make a final report that aims to reach the community. The work program of group 46 is processing corn- based tortilla chips. This topic was chosen because corn is one of the largest agricultural products in Bantul Village besides rice and soybean farming. This resource utilization program contains the steps to make corn-based tortilla chips, along with the materials needed, the estimated price of the ingredients, the estimated selling price, and the marketing methods used.